A Revolution in Endodontics: Cryotherapy - Bala, Anju; Jain, Rajnish K.; Khetarpal, Ambica; Suharwardy, Zara; Sushma; Kumar, Sandeep (Medical Science: Recent Advances and Applications Vol. 2, 2025)
Post-endodontic pain, or discomfort following root canal treatment, is a common experience among patients. Studies indicate that postoperative pain affects approximately 2.5% to nearly 60% of individuals undergoing endodontic procedures. The word CRYOTHERAPY is a mixture of two words, “cryos” meaning “cold” and “therapeia” meaning “cure”. It is widely used in the treatment of sports injury, strains, tendonitis, surgical extractions, periradicular surgeries, periodontal surgeries, implant placement, etc. It is a very simple, easy-to-apply, cost-effective treatment that reduces the usage of analgesics and antibiotics and enhances anaesthetic effect and healing response with minimal adverse effects. Nowadays, it is used in endodontics to treat post-endodontic pain. Basically, it is not simply cooling of the target tissue but rather it is transferring heat from the tissue with higher temperature to the tissue of lower temperature. Cryotherapy has three pillars of action, namely vasoconstriction, slower conduction of neural pain as well as metabolic activity of target tissue. Although cryotherapy application has some limitations, still it is gaining popularity amongst endodontists. Cryotherapy employs a multistep protocol involving this rapid freeze-thaw cycle, with repetition further potentiating tissue destruction through cellular disruption. The results of the study show that Cryotherapy reduced the incidence of postoperative pain and the need for medication intake in patients presenting with a diagnosis of necrotic pulp and symptomatic apical periodontitis. It has also been found that root canals irrigated with a cold sterile saline solution of 2.5°C for 5 min significantly mitigated post-endodontic pain (80%). In conclusion, given its ease of application, cost-effectiveness, and minimal adverse effects, cryotherapy serves as a valuable tool for enhancing the overall success of root canal therapy. Further clinical studies and long-term evaluations will help establish standardized protocols for its optimal use.